Transformative Leadership in the Sustainable Development of Early Childhood Education Teachers in South Africa: A Systematic Literature Review - Chikuvadze, Pinias; Makuvire, Claretah; Mutseekwa, Christopher; Zuva, Joseph (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – This paper sought to provide an overview and arguments of prevailing South Africa’s higher education initiatives, focusing on transformative leadership’s influence on sustainable Early Childhood Development (ECD) teacher development emphasizing partnership, empowerment, and shared vision.Design/methods/approach – This paper is grounded in a systematic review approach based on the selected keywords. 180 articles written in English and published between 2007 and 2024 in DHTE, Scopus, WoS, DOAJ, and Scielo SA databases were targeted as potential sources for this study. Systematic review guidelines were used to reduce them, focusing on topics, abstracts, and issues. The selected 80 articles were analysed independently for reliability and transferability. In addition, content analysis was used to construe the influence of transformational leadership on sustainable ECD teacher development within South Africa. Findings – The findings reveal that the rationale for adopting transformative leadership in sustainable ECD teacher development in higher education is grounded in the culture of continuous learning and professional growth.  This encourages reflection and self-assessment among teachers, helping them to evaluate their practices and adapt to meet students' needs better, which is crucial for sustainable development. In addition, this leadership style addresses social justice issues by advancing inclusive and equitable educational practices. It was acknowledged that this supports ECD teachers in developing their knowledge, skills and values. This enhances teachers’ teaching practices thereby contributing to sustainable ECD educational outcomes. Research implications/limitations – The review acknowledges the limitation of possible interpretive bias and recommends the need to explore further how transformative leadership can be adopted into the contemporary ECD curriculum. Practical implications – This provides insights for policymakers, curriculum developers, and teachers with an emphasis on how transformative leadership can influence the quality of the ECD teacher development programme in South Africa. Originality/value – This review contributes to the field by highlighting a largely overlooked transformative leadership style and suggesting how its influence can inform the creation of sustainable ECD teacher development.Paper type Literature review